Galectin-1 and Galectin-3 expression in colon cancer and its correlation with tumor invasion, differentiation, and metastatic spread - Yu. V. Kolobovnikova; O. I. Urazova; V. S. Poletika; G. V. Reyngardt; E. V. Romanova; A. V. Kurnosenko; A. I. Dmitrieva; K. I. Yankovich; M. Yu. Grishchenko (Фундаментальная и клиническая медицина)
Aim. To study the expression of galectin-1 and galectin-3 in colon cancer and the levels of these proteins in the peripheral blood in relation to the differentiation, invasion, and metastatic dissemination.Materials and Methods. We examined primary tumors and the corresponding peripheral blood samples from 81 patients with colon cancer. Control group consisted of 49 patients with colon adenoma and 17 healthy volunteers. Expression of galectin-1 and galectin-3 in colon tissue was determined by immunohistochemical staining, while their plasma level was measured by enzyme-linked immunosorbent assay. Tumor staging was performed in accordance with the TNM system (AJCC, 2009). Cell differentiation was defined according to the respective clinical guidelines (Russian Cancer Association, 2018).Results. We detected an elevated expression of galectin-1 and galectin-3 in primary colon cancer as compared with colon adenoma and higher plasma levels of these proteins in colon cancer patients in comparison with healthy volunteers. High expression of tumor and plasma galectin-1 was associated with higher tumor stage (T3/T4) and the presence of local and distant metastases. Overexpression of galectin-3 in the primary tumor correlated with lower differentiation and lymph node metastasis.Conclusion. Galectin-1 and galectin-3 are involved in colon cancer progression and might be used as predictors of an adverse outcome.